2022
DOI: 10.1002/slct.202200645
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Spectroscopic and Theoretical Analyses of Human Serum Albumin Binding to a Water‐Soluble Zinc(II) Complex including β‐Amino Alcohol

Abstract: In this study, we examined the interaction process of human serum albumin (HSA) with a water-soluble zinc(II) complex of dichloro {2-[N-(2-hydroxyethylammonioethyl) imino methyl] phenol} at pH = 7.4 and in vitro utilizing molecular docking modeling and spectral techniques. In the multi-temperature fluorescence test, the consecutive and gradual addition of the zinc(II) complex to the HSA-containing cell resulted in fluorescence quenching, and it showed that the zinc(II) complex-protein interaction is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Study of the IR spectrum of 1 revealed that there are different types of moieties in this structure for example, ν (C−H) aromatic, ν (O−H) alcoholic and ν (N−H) amine at above 3000 cm −1 , ν (C−H) aliphatic at near 3000 cm −1 and ν (C=N) imine at near 1550 cm −1 . A peak corresponding to the amine group is shifted 59 cm −1 to lower frequencies respect to the free ligand [31]. This shifts have been reported previously for alkylammonium ions [32,33] and confirming the formation of zwitterionic form of ligand.…”
Section: Spectroscopic Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…Study of the IR spectrum of 1 revealed that there are different types of moieties in this structure for example, ν (C−H) aromatic, ν (O−H) alcoholic and ν (N−H) amine at above 3000 cm −1 , ν (C−H) aliphatic at near 3000 cm −1 and ν (C=N) imine at near 1550 cm −1 . A peak corresponding to the amine group is shifted 59 cm −1 to lower frequencies respect to the free ligand [31]. This shifts have been reported previously for alkylammonium ions [32,33] and confirming the formation of zwitterionic form of ligand.…”
Section: Spectroscopic Characterizationsupporting
confidence: 87%
“…All starting chemicals and solvents (Merck, Aldrich) were used as received without further purification. The L ligand was prepared as described in previous work [31]. The infrared spectrum (as KBr pellet) in the range 400-4000 cm -1 was recorded with a Shimadzu FT-IR 8400 spectrometer.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…According to the method of Shahabadi et al [ 43 ], a certain amount of RBPI was accurately measured by freeze-dried samples and dissolved in 10 mmol/L pH 7.0 phosphate buffer to prepare 0.2 mg/mL protein solution. The solution was measured on a circular dichroic spectrometer (J-810, Japan Spectroscopic JASCO Corporation, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%